MAPPAMMANA TRADITION OF BUGINESE COMMUNITYIN BONE: A LEGAL REVIEW OF ISLAMIC INHERITANCE - Nurul Wakia (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
The mappammana tradition is a custom of the Buginese community in Bone as a form of transfer of properties from the heir to the heirs. Mappammana is a system of inheritance that has been practiced in the past to this day. The mappammana mechanism is an interesting issue, because in the millennial era, this system is still used by the Buginese community in Bone in the transfer of properties. It is important to explain the connection of the mappamana tradition in the frame of Islamic inheritance law.Research is a field of research, data sources obtained from interviews with religious leaders and figures of the Buginese community in Bone. The approach used is theological normative, sociological, and anthropological by examining the social phenomenon of the mappaammana system of the Buginese community in Bone. The findings of this study indicate that there are mappammana traditions that are general namely, pabbere and pappaseng, are gifts without any sacred value contained in the object used as maanaa.As for the mappammana, it is 'ampῑkȃle', specifically applies because ampῑkȃleis a sacred gift and is accompanied by a will. Based on Syahrur's hudud theory, at-Tufi's Maslahah, and al-Jauziayah's urf theory, mappammana as a legacy system practiced by the Buginese community in Bone is considered in line with the values of the Islamic inheritance system because it still upholds the values of consensus value and benefit.The implication of this finding is that the distribution of inheritance does not look at the way it is, but the most important thing is the pleasure of the parties in accepting the results of deliberations and distance from disputes between fellow heirs.Keywords: Islamic Inheritance Law; Tradition; Mappammana; Buginese in Bone.